Study on enhancing integrity for BLP model - LIU Yan-ming; DONG Qing-kuan; LI Xiao-ping (Tongxin xuebao)
A model which enhances the integrity of BLP model was presented based on the BLP model.This model was called as EIBLP model.Some necessary restraints to upward information flow were appended in EIBLP without chang-ing the information flow direction（down-read and up-write） of BLP model and the security axiom,access labels of sub-ject and object,access control operation mode,and state transition policy of BLP model were improved.And then,ana-lyzes the security of EIBLP was analyzed and proved.It shows that the improved EIBLP model not only satisfies com-pletely the basic security of BLP,but also enhances the integrity of BLP with improving the upward restraints,the subject and object access labels,the model operation mode,and the model state translation rules.At the same time,the improved EIBLP raises the confidentiality of BLP at a certain extent.